Fighting for Lithuanian Freedom in 1918–1920: Volunteers from Pumpėnai - Vaitkevičius, Vykintas; Stalilionis, Algimantas (Tautosakos darbai, 2017)
The article is dedicated to the volunteers of the Lithuanian army fighting for revival of the Lithuanian state. It contributes to the history of freedom research in two ways. First, the historical narrative from 1918–1920 clearly testifies that fighting for freedom presents a social challenge and indicates a threat that has immense uniting power. Second, main part of the study focuses on those who according to their free will chose to defend their Fatherland. The address of the temporary Lithuanian Government to the Lithuanian people in December 29, 1918, was essentially similar to proclamations of the uprisings of 1831 and 1863; even the means of its spreading and publication were the same. Those who responded travelled to join the army on foot or riding a horse, frequently poorly equipped, but bearing an accordion and singing songs, with firm resolve and faith in their hearts. After long years of foreign occupation, the volunteers that at first made up the whole core of the Lithuanian army, subsequently diminishing to one third of the armed forces, aspired for freedom, their own national government and establishment of the Lithuanian state. The article is based on the study of 154 participants of the fighting for Lithuanian independence from the historical Pumpėnai rural district in Panevėžys region. According to this study, young men of about 19–23 years of age formed the majority of those who responded to the appeal to stand for freedom and Fatherland in the country occupied by the Bolsheviks in the end of the 1918 – beginning of the 1919. By comparison, militia (the armed forces of the local self-defense) usually consisted of 26–29 year-old men, or even older. The age of partisans ranged from 17 to 57 years, which is a peculiar feature of the freedom fighting in northern Lithuania. Many of the latter, especially married men owning their households, returned home after the Joniškėlis region was liberated in May of the 1919. The invasion of the Bermont-led forces in July of the 1919 did not elicit any substantial response in Pumpėnai. Only in August and October of the 1920, in view of the Polish aggression, three men from Pumpėnai volunteered to join the army again (among them, Mikalojus Grabauskas volunteered for the second time). Although the land promised as reward by the government did motivate the volunteers, it was not always the main reason for their fighting. Among volunteers from Pumpėnai, there were landless workers, employees, small farmers, farmers, young people of noble origins and landowners in possession of up to 180 hectares. Afterwards many of them even did not submit an application for land. The burning enthusiasm that overfilled these young men inspiring them to join the ranks of volunteers and subsequently characterizing them as their main quality, manifested as a great desire to act, as a fighting fervor. The volunteers were under significant influence of the imagery of the great Lithuanian historical narrative and the revolutionary spirit (to use the words by Vytautas Kavolis), that ever since the 1795 united different generations of the Lithuanian freedom fighters, inspiring their children and grandchildren to continue the deeds of their fathers and grandfathers.